Mentoring and Review of the Development of Formative and Summative Assessment Tools for Economics Subjects, Accounting Material for Service Companies, Independent Curriculum for Economics Teachers of the Sekolah Indonesia Kuala Lumpur (SIKL) - Hakim, Luqman; Amirul Arif; Susanti; Bahtiar, Moh. Danang (Indonesian Journal of Society Development, 2024)
The implementation of the Independent Curriculum at Sekolah Indonesia Kuala Lumpur (SIKL) faces challenges in developing assessments that are in accordance with character education, skills, and academic demands needed in the 21st century. Therefore, this PKM program aims to provide training and mentoring to SIKL economics teachers so that they are able to compile relevant and contextual assessments. The activity took place at SIKL on July 27, 2024, from 09.00-15.00 WIB. The stages of the PKM activity include field surveys, coordination, socialization, implementation, and evaluation. This program received a positive response from SIKL teachers, who appreciated the training materials and their benefits in overcoming the difficulties of aligning character education with foreign cultural contexts. As a result, 80% of training participants were able to implement assessments according to the Independent Curriculum